2021
DOI: 10.1101/2021.09.24.461732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 spike-specific memory B cells express markers of durable immunity after non-severe COVID-19 but not after severe disease

Abstract: SARS-CoV-2 infection elicits a robust B cell response, resulting in the generation of long-lived plasma cells and memory B cells. Here, we aimed to determine the effect of COVID-19 severity on the memory B cell response and characterize changes in the memory B cell compartment between recovery and five months post-symptom onset. Using high-parameter spectral flow cytometry, we analyzed the phenotype of memory B cells with reactivity against the SARS-CoV-2 spike protein or the spike receptor binding domain (RBD… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Although we do not analyze the response of SARS-CoV-2specific B cells, several authors have reported an expansion of MBCs one-month post-symptom onset, and an increase of Sspecific IgG + switched MBC at fivemonths of follow-up. Moreover, the quality of response looks to be differential since individuals with non-severe COVID-19 have a phenotype associated with durable memory that is least frequently observed in severe COVID-19 (33). In agreement with those findings, severe COVID 19 induces an exhaustion phenotype on S1-specific IgG + MBCs compared with healthy and recovered individuals (34).…”
Section: Discussionmentioning
confidence: 66%
“…Although we do not analyze the response of SARS-CoV-2specific B cells, several authors have reported an expansion of MBCs one-month post-symptom onset, and an increase of Sspecific IgG + switched MBC at fivemonths of follow-up. Moreover, the quality of response looks to be differential since individuals with non-severe COVID-19 have a phenotype associated with durable memory that is least frequently observed in severe COVID-19 (33). In agreement with those findings, severe COVID 19 induces an exhaustion phenotype on S1-specific IgG + MBCs compared with healthy and recovered individuals (34).…”
Section: Discussionmentioning
confidence: 66%
“…In support of this, a decreased frequency of RBD-specific DN2 cells was observed 10 weeks post-infection when compared to levels during acute infection (22), suggesting that expansion of virusspecific DN2 cells is transient and resolves with infection. However, it should be noted that even five months postrecovery from severe infection, RBD-specific Double Negative B cells are still detectable (40), indicating that expansion of virally-associated DN subsets likely contracts with infection but are not lost. Furthermore, expansion of atypical memory B cells (CD27 -CD21 lo/-), which would include both DN2 and DN3 subsets, is resolved in patients recovered from severe SARS-CoV-2 infection (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of T-bet - a reliable marker of memory B cell antiviral function - is increased during SARS-CoV-2 infection, especially in symptomatic patients ( Notarbartolo et al, 2021 , Reyes et al, 2021 , Rodda et al, 2021 ), and is maintained at high levels for a few months after disease onset ( Rodda et al, 2021 ). At this point, the frequency of virus-specific T-bet + IgG + memory B cells decreases to a baseline level ( Reyes et al, 2021 ). Our data further demonstrated that T-bet + memory B cells rapidly declined in COVID-19 patients after 3 months of recovery.…”
Section: Discussionmentioning
confidence: 99%